Cellular Heterogeneity and IL-17 Pathway Dynamics Reveal Insights into the Transition from Ulcerative Colitis to Colorectal Cancer Through scRNA-Seq Analysis - Li Y; Sun R; Wang X; Ma M; Wang H; Yang B; Lu Y; Li Y (Journal of Inflammation Research)
Yaxian Li,1,* Ruochuan Sun,1,* Xiaodong Wang,2 Mengdi Ma,1 Huizhen Wang,1 Bo Yang,1 Yida Lu,3 Yongxiang Li1 1Department of General Surgery, First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 2The Robert Bosch Center for Tumor Diseases (RBCT), Stuttgart, 70376, Germany; 3Department of General Surgery, Second Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yongxiang Li, Email liyongxiangamu@163.comIntroduction: The progression of UC to CACRC involves substantial molecular and cellular alterations. A deeper understanding of these changes is essential for identifying potential therapeutic targets and improving disease outcomes.Methods: We performed scRNA-seq on tissue samples from a patient with coexisting UC and CACRC lesions, including normal colon, UC-affected tissue, and CACRC. Cell clustering, differential gene expression, and KEGG pathway enrichment analyses were conducted to characterize cellular heterogeneity and pathway dynamics.Results: Thirteen distinct cell clusters were identified, reflecting significant heterogeneity across disease stages. Six major cell types—B cells, T cells, epithelial cells, monocytes, neutrophils, and CMPs—were selected for in-depth analysis. Epithelial cells from UC samples showed marked upregulation of inflammatory genes such as IL-17A, CXCL1, IL-6, MMP3, and TNFAIP3, which were downregulated in CACRC. KEGG analysis revealed IL-17 signaling as a key pathway involved in disease progression. A progressive increase in Tregs, supported by elevated CD25 expression, was observed from normal tissue through UC to CACRC. Furthermore, C-MYC was significantly upregulated in CACRC epithelial cells, suggesting its role in tumor proliferation and metabolic reprogramming.Conclusion: This study uncovers dynamic cellular and molecular changes during the transition from UC to CACRC, highlighting IL-17 signaling, Treg expansion, and C-MYC activation as potential drivers of malignancy and targets for future therapeutic intervention.Keywords: ulcerative colitis, colorectal cancer, single-cell RNA sequencing, IL-17 signaling pathway, treg cells, epithelial cells